2023
DOI: 10.1037/xlm0001160
|View full text |Cite
|
Sign up to set email alerts
|

Metamemory judgments have dissociable reactivity effects on item and interitem relational memory.

Abstract: Making metamemory judgments reactively changes item memory itself. Here we report the first investigation of reactive influences of making judgments of learning (JOLs) on interitem relational memoryspecifically, temporal (serial) order memory. Experiment 1 found that making JOLs impaired order reconstruction. Experiment 2 observed minimal reactivity on free recall and negative reactivity on temporal clustering. Experiment 3 demonstrated a positive reactivity effect on recognition memory, and Experiment 4 detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The hypothesis that making JOLs enhances item-specific processing received further support from the finding that recall for categorized lists following JOLs was comparable to recall following two other encoding manipulations that are known to induce item-specific processing: pleasantness ratings and mental imagery. Zhao et al (2022) also found supporting evidence for the item-specific processing hypothesis using unrelated word lists. They reported that making JOLs improved performance on forced-choice recognition tests and simultaneously impaired performance on order reconstruction tests (i.e., reconstructing the temporal order in which words were encoded).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…The hypothesis that making JOLs enhances item-specific processing received further support from the finding that recall for categorized lists following JOLs was comparable to recall following two other encoding manipulations that are known to induce item-specific processing: pleasantness ratings and mental imagery. Zhao et al (2022) also found supporting evidence for the item-specific processing hypothesis using unrelated word lists. They reported that making JOLs improved performance on forced-choice recognition tests and simultaneously impaired performance on order reconstruction tests (i.e., reconstructing the temporal order in which words were encoded).…”
Section: Introductionmentioning
confidence: 52%
“…For example, in Experiments 1 and 2 of Chang and Brainerd (2023), it was observed that positive JOL reactivity for related word pairs was tied to dual-retrieval model parameters that index item-specific recollection. Moreover, according to Zhao et al (2022Zhao et al ( , 2023, item-level JOLs disrupt order reconstruction (a measure of relational processing) with unrelated word lists and rhyming pairs whose target words are categorical exemplars. However, it is worth pointing out that those stimuli (word pairs and unrelated lists) naturally trigger greater levels of item-specific processing as compared to the categorized lists we used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of word encoding, making JOLs increases the metacognitive monitoring process (Lei et al 2020) and thus enhances learning engagement (Shi et al 2023). Additionally, searching for cues to inform JOL formation also enhances item-specific processing (Chang and Brainerd 2024;Senkova and Otani 2021;Zhao et al 2023aZhao et al , 2023b, thus producing more elaborative processing. Cognitive neural activities related to learning engagement (alpha ERD) and those related to elaborative encoding (LPC amplitude and beta ERD) together contribute to the generation of the positive reactivity effect.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between reactivity and level of processing suggests that the reactivity effect may result from the fact that making JOLs induces more elaborative processing. Furthermore, it has been shown that making JOLs promotes item-specific processing of study items, in turn producing superior recall or recognition performance (Chang and Brainerd 2024;Senkova and Otani 2021;Zhao et al 2023aZhao et al , 2023b.…”
Section: Putative Mechanismsmentioning
confidence: 99%